The identity of governments in international law : aclaw - general public international law: acsa - Pavlopoulos, Niko (Oxford, United Kingdom : Publicerad:Oxford University Press, 2024)
"An abstract is a short description of your longer piece of work and is used as a free layer of content discoverable online. An abstract should not attempt to summarise the whole work as it is also there to show readers whether or not reading further is warranted. It is used to allow people searching on the internet to see that they have encountered a worthwhile 'hit'. This will encourage them to read further by clicking through to the work in full"--